(untitled) (Research, Society and Development, 2021)
This study provides reflections on the hybridisation of paradigms resulting from the creation of the Academy of Health Programme created by the Brazilian National Ministry of Health. This was a descriptive study, analysing the National Health Promotion Policy (first published in 2006 and revised in 2014), the National Strategic Action Plan to Battle Chronic Non-Communicable Diseases (NCDs) and the Academy of Health Programme (established by Ordinance no. 719/GM/MS in 2011). The scientific disputes seen during the development of the programme have had an impact on the practices it advises and on its implementation. We reflect that the Academy of Health Programme can and should create a space where, beyond the chronic NCDs, the model of dominator and dominated can be subverted and the transformation idealised by collective health through the health promotion movement can be made concrete.